2023
DOI: 10.1039/d2cp04825f
|View full text |Cite
|
Sign up to set email alerts
|

A rotational investigation of the three isomeric forms of cyanoethynylbenzene (HCC-C6H4-CN): benchmarking experiments and calculations using the “Lego brick” approach

Abstract: The recent detection of several aromatic nitriles in the interstellar medium brings new interest into the laboratory spectroscopy of this family of molecules. Here, we report the study of three...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In line with Ye et al (2022), the computed B 0 values were found to deviate from experiment, on average, by 0.026%. The discrepancy increased to 2.5% for quartic centrifugal terms (Spaniol et al, 2023). The experimental spectroscopic data obtained by Spaniol et al (2023) will enable astronomical searches for these molecules.…”
Section: Figure 10mentioning
confidence: 96%
See 3 more Smart Citations
“…In line with Ye et al (2022), the computed B 0 values were found to deviate from experiment, on average, by 0.026%. The discrepancy increased to 2.5% for quartic centrifugal terms (Spaniol et al, 2023). The experimental spectroscopic data obtained by Spaniol et al (2023) will enable astronomical searches for these molecules.…”
Section: Figure 10mentioning
confidence: 96%
“…The discrepancy increased to 2.5% for quartic centrifugal terms (Spaniol et al, 2023). The experimental spectroscopic data obtained by Spaniol et al (2023) will enable astronomical searches for these molecules.…”
Section: Figure 10mentioning
confidence: 96%
See 2 more Smart Citations
“…In the previous decades, not only more computational resources have become available during the information revolution, but also the accuracy of quantum chemical calculations has been significantly increased, and is still improving continuously with newer and more elaborate theoretical conceptualizations. Several benchmarking studies involving tight collaborations between microwave spectroscopic and theoretical groups have been successfully established, aiming to predict the experimental rotational constants with even higher accuracy [12][13][14][15][16][17]. On the one hand, this joint-venture allows experimentalists to efficiently assign the microwave spectra and to access detailed molecular geometries in the cases when minor isotopologue spectra are lacking.…”
Section: Introductionmentioning
confidence: 99%